Social vulnerability assessment for disaster risk reduction and management planning the case of the lakeshore barangays in the municipality of Pila, Laguna - Rizal, Ma. Narcielyn P. (School of Urban and Regional Planning, University of the Philippines Diliman, 2024)
This study aimed to assess the social vulnerability of the residents in the lakeshore barangays of the Municipality of Pila, Laguna (Barangays Aplaya, Bagong Pook, Linga, Pinagbayanan, and Tubuan) to flooding as input to the municipality's disaster risk reduction and management planning. A total of 385 households from the lakeshore barangays participated in the household survey. Key Informant Interviews (Kils) with the Municipal Disaster Risk Reduction and Management Officer (MDRRMO) and barangay officials, and Focus Group Discussions (FGDs) with select barangay residents, were also conducted to validate and supplement the survey results. This study identified 28 factors (e.g., Duration of Flooding for Exposure, Age for Sensitivity, and Employment Status for Adaptive Capacity), each with several indicators. Vulnerability values were assigned to the indicators under each factor, based on the factor's functional relationship with social vulnerability. These values were then used to calculate the factor indices, component indices, and overall social vulnerability index. No a priori assumption was made about the relevance of each indicator to its factor, each factor to its social vulnerability component, and each component to the overall social vulnerability index, hence no weights were attached to the individual indicator, factor, and component scores. Meanwhile, Kendall's test of concordance was done to measure the agreement among the lakeshore barangays regarding the ranking of the social vulnerability factors. Following the specific objectives of the study, results showed that the five lakeshore barangays are moderately exposed, moderately sensitive, and moderately adaptive, with an overall social vulnerability index of 0.41, indicating that they are moderately vulnerable to flooding. It was found that Barangay Aplaya is the most socially vulnerable, while Barangay Tubuan is the least socially vulnerable. The factors perceived to influence social vulnerability the most based on the ranking of the lakeshore barangay residents are: (1) capacity building, (2) family structure, (3) social networks, (4) education level, and (5) duration of flooding. These results can serve as inputs to local management planning imperatives and practices in the municipality and the lakeshore barangays, as they can be used to identify gaps and determine measures to address these gaps. The results can also guide the national government in crafting policies that govern local disaster risk reduction and management planning. The hypothesis that high adaptive capacity level helps decrease social vulnerability is accepted, as the residents' high adaptive capacity contributed to lowering their social vulnerability level despite their relatively high level of exposure and sensitivity. Meanwhile, among the hypothesized factors that tend to shape social vulnerability the most, only flood duration/duration of submersion under exposure, and education level and social networks under adaptive capacity, are accepted. Lastly, the null hypothesis that the five lakeshore barangays are not concordant with one another is rejected. It was found that the five lakeshore barangays agree on the rankings of the social vulnerability factors in terms of how they affect their overall social vulnerability. It is recommended that the municipality and barangays utilize the ranking of factors in the prioritization of interventions to address their social vulnerability. The municipal government should also continue or enhance initiatives related to factors with high adaptive capacity indices such as the quality of medical services and access to information. Lastly, the municipal government should prioritize reducing the social vulnerability of Barangay Aplaya as it is identified as the most vulnerable barangay.